Bilingual students’ mother tongue – a resource for teaching and learning mathematics - Norén, Eva (NOMAD Nordic Studies in Mathematics Education, 2008)
This article presents some of the main results of a bilingual mathematics teaching project, which run in five multicultural schools in Sweden. The main research question was: How do mathematical practices emerge in bilingual mathematics classrooms? In the project bilingual mathematics teachers seemed to promote mathematical learning and engagement in the classroom by using two languages in mathematical discourses. Pupils and teachers communicated mathematically in different ways, and the interplay between mathematics and language often became obvious. Bilingual pupils participating in the project expressed that they were able to learn more and they felt secure with the ways of using languages and learning mathematics. Participating in the project gave many of the pupils’ confidence in their mathematics learning competence.